AB0050 Irf8 Promotes TH17 Differentiation via Activation of Integrin-Mediated Tgfbeta Signaling in Neuroinflammation. (10th June 2014) - Yoshimi, R.; Yoshida, Y.; Yoshii, H.; Kim, D.; Dey, A.; Xiong, H.; Munasinghe, J.; Yazawa, I.; O'Donovan, M.J.; Maximova, O.A.; Sharma, S.; Zhu, J.; et al.
Abstract : Background: There is accumulating evidence that Th17 cells promote inflammation and tissue injury in many autoimmune diseases. Although recent epidemiological studies identified IRF8 as a susceptibility factor for the autoimmune diseases, such as systemic lupus erythematosus 1 and multiple sclerosis 2, it has remained unknown how IRF8 influences the role of Th17 cell expansion in the pathogenesis. Objectives: Here we investigated the role of IRF8 in Th17 differentiation using mice with experimental autoimmune encephalomyelitis (EAE), a model of multiple sclerosis. Methods: Wild-type (WT), conventional Irf8 –/–, and two conditional Irf8 –/– mice, Irf8 f/f mice with LysM-cre and those with Lck-cre, were injected with MOG35–55 and clinical sign of the EAE were scored. The mRNA levels of cytokine and transcription factor genes and the populations of immune cell subsets in lymph nodes, spleens, and spinal cords were measured by qPCR and flow cytometry. Luciferase reporter assays and chromatin immunoprecipitation (ChIP) assays were performed to test IRF8 regulation of Itgb8 transcription. We examined in vitro development of Th17 cells from naïve CD4 + T cells cultured with CD11c + dendritic cells (DCs) in the presence of latent TGFβ. Results: Irf8 –/– mice were resistant to EAE and failed to generate Th1, Th17 and Treg cells after MOG injection. Irf8 f/f mice with LysM-cre remained resistant to EAE, while those with Lck-cre showed similar clinical scores as WT mice, indicating that IRF8 in APCs, but not in T cells, is responsible for causing EAE. The levels of Il12b, a subunit of IL-12p70 and IL-23, greatly increased in WT mice, but not in Irf8 –/– mice, during EAE. The increase in IL-27 production in Irf8 –/– mice was observed, indicating that IRF8 creates IL-12 family cytokine milieu favoring EAE. On the other hand, Itgb8, an integrin molecule important for Th17 differentiation via TGFβ activation, was highly expressed and in WT APCs, but was much lower in the Irf8 –/– counterparts. The reporter containing Itgb8 upstream fragment gave robust luciferase activity when co-transfected with Irf8 vector. Luciferase assays and ChIP assays showed that Itgb8 is a direct target of IRF8 which activates Itgb8 transcription. With latent TGFβ, WT DCs, but not Irf8 –/– DCs, stimulated Th17 differentiation. Conclusions: This study shows that IRF8 is essential for Th17 cell development by controlling the production of IL-12 family cytokines and by activating TGFβ signaling in APCs. References: BIOLUPUS Network, GENLES Network. Identification of IRF8, TMEM39A, and IKZF3-ZPBP2 as susceptibility loci for systemic lupus erythematosus in a large-scale multiracial replication study. Am J Hum Genet 2012;90:648-60. International Multiple Sclerosis Genetics Consortium (IMSGC). Analysis of immune-related loci identifies 48 new susceptibility variants for multiple sclerosis. Nat Genet 2013;45:1353-60. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3457